Pengaruh Komitmen dan Iklim Organisasi terhadap Kepuasan Kerja Karyawan pada Unit Kerja Packhouse PT. Holcim Indonesia Tbk. Cilacap - Werdiasih, Rustina Dewi; Baruwarso, Isnaintoro (JURNAL EKONOMI, 2016)
Isnaintoro Baruwarso from Management, STIE Muhammadiyah Cilacap. This research is entiled â€œThe effect of Organization Climate and Commitment on Employes Job Satisfaction at the Section Packhouse of the PT. Holcim Indonesia Tbk. Cilacapâ€.Â The objectif research are fisrt to find and analyze the effect of organization climate and commitment on employees job satisfaction and than to find and anlyze the variabel that has the greatest effect on employees job satisfaction of the Section Packhouse at the PT. Holcim Indonesia Tbk. Cilacap.The proposed hypotheses of research are:Commitment have significant effect on employees job Satisfaction.Organization Climate have significant effect on employees job sastifaction.Commitment and organiation climate together have a significant effect on employees job sastifaction.Oganization climate variable have the greatest effect on employees job satisfaction.Â Â Â Â Â Â Â Â Â Â Â Than organization commitment variable of the Section Packhouse at the PT. Holcim Indonesia Tbk Cilacap. The instrument of analysis in thisÂ research are,Â F â€“test , t â€“ test and beta standarized coefisien test.Â Â Â Â Â Â Â Â Â Â Â Based of the result of research and data analysis , it has gotÂ computed â€“F 57,238 and F-table 3,354 and probabilytas (p) = 0,000 so computed â€“F is greater than F-table (57,238 > 3,354). Than of the result of t-test, it have got value ofÂ t1 (3,234) and t2 ( 3,856), greater of the value of t â€“ table (2,042) so the first hypotheses mentioned that organization climate and commitment variables have significant effect on employees job satisfaction is accepted. Next from the result of koeficien beta standarized test, is got value variable of organization climate (0,499) is greater than variable of commitment (0,419). Therefore the scond hypotheses mentioned that organization climate variable has greater effect on employees job satisfaction variable at the section Packhoue PT. Holcim Indonesia Tbk. Cilacap.Â Â Â Â Â Â Â Â Â Â Â From the conclusions, the research implications are support from management have been significant effect on employees job satisfaction and managementÂ has to increase motivator and implementasion of the job satisfaction for employees. Then management PT. Holcim Indonesia has to pay more attention and increase organization climate variable in order to get higher jo satisfaction from its employees.Â Keyword: commitment, organizational climate, job satisfaction.